Tātwīr wā Tātbīq Kutāīb kā Wāsāīl āl-Mubtākārāt līī Tāhsīn āl-Māhārāt āl-Kītābāh - Primaningtyas, Mega; Kusuma, Alam Budi; Anggasta, Reo; Hassan, Abdal Rahman Mohammad Teama (Al Maghazi : Arabic Language in Higher Education, 2025)
Mastery of vocabulary is a crucial foundation in language learning, including Arabic, especially for non-native speakers. The main challenge often faced is the difficulty of memorizing and actively using vocabulary, particularly in the skill of kitabah (writing). In response to this challenge, this study aims to develop and implement an innovative learning medium called Kutaib (a pocketbook) as a supporting tool to enhance Arabic writing skills. The Kutaib is designed with a contextual approach that includes thematic vocabulary and simple writing exercises, enabling students to more easily remember and use the words in sentences. This research was conducted at Pondok Pesantren Ma’arif Nurul Haromain Kulon Progo using a Research and Development (R&D) method through several stages: needs analysis, design, limited trials, and evaluation. The implementation involved socialization and demonstration activities to train students in using the Kutaib during daily learning sessions. The findings show that the use of Kutaib successfully increased students’ motivation and writing skills, as evidenced by the growth in the quantity and variety of vocabulary used in their kitabah exercises. However, the study also identified a limitation—insufficient continuous teacher supervision—which affected the consistency of the medium’s application. Therefore, ongoing collaboration between researchers and educators is needed to systematically integrate the Kutaib into the teaching and learning process. In conclusion, the development and implementation of Kutaib proved to be an effective and innovative learning medium for improving students’ kitabah skills in the pesantren learning environment.